2014
DOI: 10.4314/jae.v18i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Information and Training Sources Used by Rice Farmers in North Central Nigeria

Abstract: The study investigated the information and training sources used by rice farmers in North central, Nigeria. A total of 320 respondents were selected and interviewed using structured interview schedule. The respondents were of two categories, the participants and non-participants of the intervention programme. The data were analyzed using frequency, percentages, mean, ranking and chi square. Majority (80.6%) of the non-participants had been cultivating rice for more than 20 years and it was only few (10%) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This information available to farmers usually comes from different sources, which more often than not influences utilization of technologies and packages. Tsado et al (2014) found that some farmers use limited information sources, while others give themselves to being more influenced by certain information channel during different stages of innovation adoption. However, adequate information which usually abounds through a variety of sources has been identified as one of the major pre-requisite for widespread acceptance of agricultural innovation (Agbamu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This information available to farmers usually comes from different sources, which more often than not influences utilization of technologies and packages. Tsado et al (2014) found that some farmers use limited information sources, while others give themselves to being more influenced by certain information channel during different stages of innovation adoption. However, adequate information which usually abounds through a variety of sources has been identified as one of the major pre-requisite for widespread acceptance of agricultural innovation (Agbamu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Training is mostly directed at improving the ability of individuals to do vocation more effectively and efficiently. Generally, it involves acquiring information, knowledge and developing abilities or attitudes, which will result in greater competence in the performance of a work (Tsado et al, 2014). In order to make any training meaningful and effective, it is imperative on the part of the training organizers to identify the training needs of the farmers based on which a suitable training module can be developed so that the appropriate training is given and higher degree of productivity and profitability can be achieved (Chawang and Jha, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted for this purpose in different regions of the world, such as (Bajpai et al, 2007;Chawang and Jah, 2010;Nath and Chowdhury, 2010;Devarani, 2013) in India, (Tologbonse et al, 2008;Alarima et al, 2011;Tsado et al, 2014) in Nigeria, (Nahfees, 2013) in Sri Lanka, (Goli et al, 2013) in Iran, (Benard et al, 2014) in Tanzania. These studies indicate that the major areas of training needs of the rice growers were: plant protection measures, fertilizer management, loan and intercultural operation, winnowing, threshing, insect and disease management, water management, weed management, land preparation, sowing and transplanting, harvesting and storage, surface leveling and smoothening, nursery management, selection of high yielding varieties, selection of healthy seeds, marketing.…”
Section: Introductionmentioning
confidence: 99%